Hydrogen Sulfide Mediating both Excitatory and Inhibitory Effects in a Rat Model of Meningeal Nociception and Headache Generation - Teicher, Christiane; De Col, Roberto; Messlinger, Karl (Frontiers in Neurology, 2017)
Background/Purpose: Hydrogen sulfide (H2S) is a neuromodulator acting through nitroxyl (HNO) when it reacts with nitric oxide (NO). HNO activates TRP channels of the ankyrin type 1 (TRPA1) causing release of calcitonin gene-related peptide (CGRP) from primary afferents. Activation of meningeal nociceptors projecting to the human spinal trigeminal nucleus may lead to headaches. In a rat model of meningeal nociception, the activity of spinal trigeminal neurons was used as readout for the interaction between H2S and NO. Methods: In anesthetized rats extracellular recordings from single neurons in the spinal trigeminal nucleus were made. Na2S producing H2S in the tissue and the NO donor DEA-NONOate were infused intravenously. H2S was also locally applied onto the exposed cranial dura mater or the medulla. Endogenous production of H2S was inhibited by oxamic acid and NO production was inhibited by L-NAME to manipulate endogenous HNO formation. Key Results: Systemic administration of Na2S was followed either by increased ongoing activity (in 73 %) or decreased activity (in 27 % of units). Topical application of Na2S onto the cranial dura mater caused a short-lasting activation followed by a long-lasting decrease in activity in the majority of units (70 %). Systemic administration of DEA-NONOate increased neuronal activity, subsequent infusion of Na2S added to this effect, whereas DEA-NONOate did not augment the activity after Na2S. The stimulating effect of DEA-NONOate was inhibited by oxamic acid in 75 % of units, and L-NAME following Na2S administration returned the activity to baseline. Conclusions: Individual spinal trigeminal neurons may be activated or (less frequently) inhibited by the TRPA1 agonist HNO, presumably formed by H2S and NO in the spinal trigeminal nucleus, whereby endogenous H2S production seems to be rate-limiting. Activation of meningeal afferents by HNO may induce decreased spinal trigeminal activity, consistent with the elevation of the electrical threshold caused by TRPA1 activation in afferent fibers. Thus, the effects of H2S-NO-TRPA1 signaling depend on the site of action and the type of central neurons. The role of H2S-NO-TRPA1 in headache generation seems to be ambiguous.